2022
DOI: 10.1038/s41598-022-23078-z
|View full text |Cite
|
Sign up to set email alerts
|

WARS1, TYMP and GBP1 display a distinctive microcirculation pattern by immunohistochemistry during antibody-mediated rejection in kidney transplantation

Abstract: Antibody-mediated rejection (ABMR) is the leading cause of allograft failure in kidney transplantation. Defined by the Banff classification, its gold standard diagnosis remains a challenge, with limited inter-observer reproducibility of the histological scores and efficient immunomarker availability. We performed an immunohistochemical analysis of 3 interferon-related proteins, WARS1, TYMP and GBP1 in a cohort of kidney allograft biopsies including 17 ABMR cases and 37 other common graft injuries. Slides were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Using microdissection on formalin-fixed kidney allograft biopsies combined with mass spectrometry-based proteomics, it was recently reported that 77 proteins were deregulated in glomerulitis compared to stable grafts, particularly involved in cellular stress mediated by interferons type I and II, leukocyte activation and microcirculation remodeling 55 . Also here, WARS1 protein was overexpressed in leucocytes infiltrating the glomeruli as well as in endothelial cells during ABMR 55,56 . Furthermore, our cell-to-cell communications analysis suggested that CXCL10 overexpression by FcγRIII+ monocytes may recruit CXCR3 + T cells and activate ACKR1+ endothelial cells composing the peritubular capillaries.…”
Section: Discussionmentioning
confidence: 57%
“…Using microdissection on formalin-fixed kidney allograft biopsies combined with mass spectrometry-based proteomics, it was recently reported that 77 proteins were deregulated in glomerulitis compared to stable grafts, particularly involved in cellular stress mediated by interferons type I and II, leukocyte activation and microcirculation remodeling 55 . Also here, WARS1 protein was overexpressed in leucocytes infiltrating the glomeruli as well as in endothelial cells during ABMR 55,56 . Furthermore, our cell-to-cell communications analysis suggested that CXCL10 overexpression by FcγRIII+ monocytes may recruit CXCR3 + T cells and activate ACKR1+ endothelial cells composing the peritubular capillaries.…”
Section: Discussionmentioning
confidence: 57%
“…Increased mRNA levels of WARS are reported to be associated with renal rejection [ 52 ]. Using a proteomic approach, one study found that high expression of the interferon associated protein WARS1 could be used as a specific indicator of endothelial stress along with TYMP and GBP1 to aid in the diagnosis of ABMR [ 53 , 54 ]. Our study also demonstrates its important potential diagnostic value in kidney transplant rejection and long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…GBP1 is highly expressed in macrophages, endothelial cells, and epithelial cells, with continued high expression levels in T cells after IFN-γ stimulation induced by interferon-γ (IFN-γ) 32 . In several studies of renal transplant rejection, researchers have con rmed through transcriptomic analysis and tissue biopsies that GBP1 may serve as a biological characteristic and predictive model for acute rejection [33][34][35] . Recent research have found that GBP1 binds to lipopolysaccharide (LPS) during bacterial infection, mediating the recruitment and activation of in ammatory caspase-4 through cleavage of GSDMD to induce pyroptosis 36,37 .…”
Section: Discussionmentioning
confidence: 99%